Effect of sad text on blood pressure - OĞUZ, SIDIKA; ÇAMCI, GÜLŞAH (My University, 2015)
bjective: To determine experimentally whether reading sad text increases blood pressure of individuals or not. Methodology: This cross sectional study was performed at Health Care Center Turkey. Adults who had referred to public health center were included in this study between 1st December 2014 to 28th February 2015. Data of blood pressure measurements and questionnaire were recorded. At first, subjects were taken into a quiet room and had rest for five minutes in sitting position. Before reading sad text and blood pressure was measured on the right arm. Then a sad text of 900 words was read by the volunteer and as soon as it was finished, blood pressure was measured again. Data were analyzed with percentage, frequency, variance analysis, student's t-tests. Results: About 45 adults were included in the study . Mean age of individuals was 43.4±13.8 years and 55.6% of them were females and 35.6% had hypertension. Average systolic blood pressure of first measurement was 123.91±5.58 mm Hg, average diastolic blood pressure was 75.44±5.07 mm Hg. There was no difference when diastolic blood pressure values were compared before and after sad text reading for the subjects (p=.64). There was significantly difference when systolic blood pressure values were compared before and after sad text reading for the subjects (p=.00). Conclusion: After reading a sad text, systolic blood pressure of individuals increased.
Keywords: KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); Hypertension; Blood Pressure; Sad Text